2018
DOI: 10.1016/j.vaccine.2017.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Measles and Rubella Global Strategic Plan 2012–2020 midterm review

Abstract: 1. Measles eradication is the ultimate goal but it is premature to set a date for its accomplishment. Existing regional elimination goals should be vigorously pursued to enable setting a global target by 2020. 2. The basic strategic approaches articulated in the Global Measles and Rubella Strategic Plan 2012-2020 are valid to achieve the goals but have not been fully implemented (or not appropriately adapted to local situations). 3. The report recommends a shift from primary reliance on supplementary immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 0 publications
0
54
0
8
Order By: Relevance
“…Universal immunization programs have been implemented in many countries worldwide and have significantly lowered the incidence and spread of infectious disease. The effective measles, mumps, and rubella (MMR) vaccine is widely administered globally (); however, recent studies have demonstrated a decline in protective antirubella antibodies in countries with universal vaccination program, including among women of reproductive age—thus increasing the risk of rubella infection and severe birth defects due to congenital rubella syndrome ().…”
mentioning
confidence: 99%
“…Universal immunization programs have been implemented in many countries worldwide and have significantly lowered the incidence and spread of infectious disease. The effective measles, mumps, and rubella (MMR) vaccine is widely administered globally (); however, recent studies have demonstrated a decline in protective antirubella antibodies in countries with universal vaccination program, including among women of reproductive age—thus increasing the risk of rubella infection and severe birth defects due to congenital rubella syndrome ().…”
mentioning
confidence: 99%
“…За оцінками експертів Всесвітньої організації охорони здоров'я (ВООЗ), саме вакцинація проти кору упродовж 2000-2016 років призвела до зниження захворюваності на 75 %, а рівня смертності від кору - на 79 %, запобігши 20,4 млн смертей [2,3], тоді як у 20-х роках ХХ сторіччя рівень смертності сягав 30 % серед усіх інфікованих осіб [4]. Завдяки вакцинопрофілактиці та розвитку системи охорони здоров'я показник смертності зменшився до 0,5 % у розвинених країнах, а в країнах із низькими соціальним рівнем розвиненості медичної допомоги цей показник може коливатись від 10 до 20-30 % [5]. Розробка й застосування безпечних й ефективних живих атенуйованих противірусних вакцин, а також поширення імунізації призвели до зни-ження показників смертності від кору на 60-75 %, особливо серед дітей до 5 років (на 25 %) [6,7].…”
Section: оригінальні дослідження вступunclassified
“…Epidemiological investigations by local and state health departments identified 31 total cases of measles in 22 detainees and nine staff members. Without any doubt, this finding highlights the necessity for primary reliance on supplementary immunization activities (SIAs) to assure two doses of measles-containing vaccine (MCV) administration in customs officers, which constitute a 'high-risk' occupational group for measles transmission (22).…”
Section: Customs Officers and Viral Infectionsmentioning
confidence: 99%